Dynamics of Agrophysical Parameters and Corn Yield Under Minimum Tillage in Samarkand Region - Syromiatnykov Yurii; Khalilov Nasridin; Troyanovskaya Irina; Voinash Sergey; Gulyarenko Alexandr; Malikov Vladimir; Orekhovskaya Alexandra (Acta Technologica Agriculturae)
Minimal tillage is becoming increasingly important in arid regions. The purpose of this study is to study the effects of different tillage methods on soil agrophysical parameters and corn yield. The main agrophysical parameters of the soil were density, hardness, and moisture. The field experiment was conducted in the Samarkand region of Uzbekistan from 2020 to 2022. The region is characterised by a continental climate, with hot and dry summers and mild winters. The experiment compared the following tillage methods: deep ploughing, shallow flat-cutting, shallow disc tillage, shallow disc tillage with direct seeding, and no-till. Soil parameters were measured at different depths (0–10 cm, 10–20 cm, 20–30 cm) at three stages of corn growth (before sowing, at the 12–13 leaf stage, and at the stage of full grain maturity). As a result, it was found that soil density with shallow surface tillage remains almost unchanged and is 1.07–1.08 g·cm−3. With deep ploughing, soil density increases from 1.014 g·cm−3 at the depth of 0–10 cm to 1.094 g·cm−3 at the depth of 20–30 cm. Soil hardness with deep ploughing increases from 26.145 kg·cm−2 at the depth of 0–10 cm to 35.445 kg·cm−² at the depth of 20–30 cm. Soil moisture gradually decreases with depth with all types of tillage, with deep ploughing showing a slightly greater decrease in moisture (by 7–8% for every 10 cm of depth) compared to shallow tillage. Deep ploughing results in greater compaction and moisture loss in the deeper soil layers. Shallow disc tillage with direct seeding provided the highest maize yield of 7.10 t·ha−1, while no-till showed the lowest yield of 5.41 t·ha−1.